Peran Belanja Pemerintah Daerah Dalam Memoderasi Pengaruh Zakat Terhadap Kemiskinan di Provinsi Aceh - Nur Azizah Siregar; Khairul Amri; M. Haris Riyaldi (Journal of Law and Economics, 2023)
This research article reviews the role of local government spending in moderating the relationship between zakat receipts and poverty in 23 districts / cities in Aceh province for the 2009-2018 period. The type of data in this study is secondary data in the form of panel data, namely a combination of time series data and cross section data. Sources of data were obtained from BPS Aceh, Baitul Mal Aceh and the Regional Government processed by the Regional Financial Data Sub-Directorate, Directorate of EPIKD from 2009-2018. The method of research analysis was carried out using panel data regression analysis and MRA to examine the effect of zakat and regional spending on poverty reduction and to examine the role of regional spending in moderating the relationship between zakat and poverty in Aceh Province. The results showed; (1) zakat has a negative and significant effect on poverty reduction; (2) BPD has a negative and significant effect on poverty reduction; (3) MDR is negative and not significant to the relationship between zakat and poverty, which means that BPD is only an independent variable but not a moderating variable on the relationship between zakat and poverty